Assessment of the effect of drying methods on the chemical composition and in vitro gas production of two woody species - Parissi Z.M.; Nastis A.S.; Tsiouvaras C.N.; Khazaal K. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
The effect of the drying method on the forage quality of two browse species (Arbutus unedo and Robinia pseudoacacia) was investigated at three phenological stages. Hand-picked samples were dried either in oven or under frozen conditions (freeze-drying). The chemical composition of the samples was determined and their nutritive value was assessed using the in vitro gas production technique after incubation. Fermentation kinetics was described. The crude protein (CP) content was always higher in R. pseudoacacia than in A. unedo. When maturating, CP decreased in both R. pseudoacacia and A. unedo while Neutral Detergent Fibre (NDF) and lignin content increased. Freeze-drying had no effect on CP but resulted in lower concentrations of NDF and lignin. The drying method did not affect gas production in A. unedo. However, freeze-dried R. pseudoacacia produced a higher volume of gas at all phenological stages. It was concluded that the drying technique could affect the chemical composition and fermentation of animal feeds. Furthermore, fermentation characteristics and CP content of R. pseudoacacia make it a promising fodder species for livestock.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)